Fleeing persecution: a study on LGBTQI+ asylum in Europe and Germany - Zanin, Henrique da Silveira (2022)
In a world that still persecutes, marginalises and discriminates LGBTQI+ individuals, and asylum seekers and refugees are denied rights and have their basic humanity violated, this dissertation intended to understand whether the German government develops asylum policies specifically tailored to the needs of LGBTQI+ asylum seekers and refugees and whether the literature has addressed the implementation of such policies across the European continent. LGBTQI+ asylum is a rather new field of research, as the first judicial decisions on that matter are from the 1990s. Among the European states, Germany has been more open to asylum than other states in the continent and has received the worlds highest number of asylum seekers between 2010 and 2019, which justifies the interest in researching the asylum policies in place in that state beyond investigating the European scenario in general. The research was developed through a qualitative approach, combining theoretical and empirical analyses, as well as a systematic literature review and an interview with the director of the German LGBTQI+ asylum programme. Among the categories created herein, we observe that there are similarities between Europe and Germany regarding the focus of the literature on infrastructure, training and advice, stereotypes, and NGO support. Germany seems to have a structured programme specifically created to meet LGBTQI+ asylum seekers and refugees needs, but states in general still seem to lack social inclusion policies, as discrimination, homophobia, transphobia, and xenophobia are generalised social issues that permeates many European states. This dissertation hopes such a summary of European good practices and literature suggestions is taken into consideration by states around the world in order to make sure they are addressing LGBTQI+ asylum in an appropriate manner that respects individuals personal characteristics and humanity.